Patient engagement or information overload: patient and physician views on sharing the medical record in the acute setting - Fritz, Zoë (Clin Med (Lond), 2019)
Background: Patient and professional views about the impact of providing full real-time access to the medical record in the in-hospital setting are unknown. Methods: Likert-scale and free-text validated questionnaire survey of physicians and patients from acute medical units in two hospitals. The questionnaire explored recent experiences; views on the formation of trust, and views on sharing either the entire medical record or a summary. Results: Two-hundred and forty-eight patient questionnaires (62% response rate) and 32 physician questionnaires (21% response rate) were returned. Twenty-seven per cent of patients did not recall being told their diagnosis. Doctors and patients differed on what practices that they believed built trust. Eighty-one per cent of patients supported the idea of having access to the full medical record (for empowerment; the right to information about oneself; as an aide-memoire for discussion). Doctors feared it might provoke anxiety and change the nature of what was written. A written lay summary record was preferred by doctors and patients. Conclusions: The current system of providing information verbally to patients is inadequate. Patients want more information and are less concerned than physicians about potential negative effects of real-time access to their records. Patient access to medical records (in both full and summary forms) should be evaluated.